A252 THE DIETARY FIBRE, RHAMNOGALACTURONAN (RGAL), DRIVES AN INFLAMMATORY GENE EXPRESSION PROFILE IN INTESTINAL EPITHELIAL CELLS - Shang, J (J Can Assoc Gastroenterol, 2019)
BACKGROUND: Impaired mucosal healing in the intestinal epithelium has been linked to inflammatory bowel disease (IBD). While the resolution of inflammation was historically perceived to be a passive process of mucosal healing, we have begun to appreciate that cells and mediators that have traditionally been considered pro-inflammatory, are also crucial in the resolution of inflammation. Specifically, recent evidence suggests that neutrophils, while important contributors to acute inflammation, are also key elements in the pro-resolution microenvironment that promotes mucosal healing in the inflamed gut. Our previous data have shown that administration of the dietary fibre, rhamnogalacturonan (RGal), reduces disease severity in a murine model of DSS colitis. Additionally, apical treatment of the Caco-2 human intestinal epithelial cell line with RGal induces an increase in transepithelial electrical resistance (TER) and accelerates wound-healing in vitro. AIMS: We hypothesized that RGal promotes a healing response in epithelial cells via the production of mediators that contribute to the establishment of a pro-resolution microenvironment. The aims of this project are to (1) Characterize the receptor(s) and signalling pathways activated by RGal in intestinal epithelial cells and (2) determine the ability of RGal to create a pro-resolution inflammatory milieu and mediate neutrophil-epithelial interactions. METHODS: In order to determine the transcriptionally dependent effects of RGal on epithelial function, Caco-2 monolayers were treated apically for 6, 12 and 24h with RGal, and RNA collected for transcriptome sequencing. Genes with changes in expression more than 3-fold were entered into Enrichr for pathway analysis. In order to confirm changes in protein expression from transcriptome sequencing data, Meso Scale Discovery (MSD) multi-array immunoassay was performed. RESULTS: RGal differentially induced changes in gene expression 6, 12 and 24h post-treatment. While RGal had no significant effect on tight junction gene expression 6h post-treatment, RGal upregulated the expression of inflammatory response genes including neutrophil regulatory genes (CXCL1, 243.9-fold; CXCL2, 15.2-fold; CXCL3, 58.8-fold; CXCL5, 57-fold; CXCL8, 515.6-fold; G-CSF, 18-fold; n=3; p<0.05). Consistent with gene expression data, MSD multi-plex immunoassay revealed an upregulation in CXCL8 family chemokines. For example, CXCL8 production was increased in cell lysates 116.1-fold 2h post-treatment (n=3; p<0.01) and secretion of CXCL8 was increased 11.8-fold in cell supernatants 8h post-treatment (n=3; p<0.05). CONCLUSIONS: RGal drives the expression of neutrophil regulatory genes in intestinal epithelial cells. Thus, RGal may contribute a pro-resolution inflammatory milieu by facilitating neutrophil-epithelial interactions. FUNDING AGENCIES: Natural Sciences and Engineering Research Council of Canada (NSERC); The American Physiological Society (APS)